Dampak Kemudahan, Impulsive Buying dan Risiko terhadap Keputusan Pembelian dalam Penggunaan Shopee Paylater - Maria Y Aryati Wahyuningrum (Soratekno Publisher, 2025)
The development of internet technology has created a significant transformation in consumer behavior through easier access to digital transactions. One innovation that has played a key role in this change is the Paylater service, specifically Shopee Paylater, which offers easy installment payments without the need for a credit card. Among e-commerce users, this phenomenon has led to an increase in impulsive purchasing and consumer behavior. This study aims to determine the influence of convenience, impulsive buying, and risk on purchase decisions using Shopee Paylater. The analysis method used in this study was primary data, using a purposive sampling technique. The questionnaire was distributed online to 100 Shopee Paylater users in the Bekasi region. The data analysis tool used was IBM SPSS Statistics 26, which included validity and reliability tests, classical assumption tests, and multiple linear regression. The results showed that convenience, impulsive buying, and risk partially and simultaneously influenced purchase decisions using Shopee Paylater.